PENERAPAN MATEMATIKA PADA ILMU EKONOMI : HIMPUNAN - Alvina Salva Salsabila; Agif Masfahrizal; Fardan Putra Dharmawan; Lailatul Fitriyah; Maylani Dwi Mawardani; Vivi Yuliawati (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study explores the role of mathematics in economics, focusing on the application of set theory and market equilibrium models. (1) Set theory provides a framework for organizing economic data and analyzing relationships between variables, such as market segmentation and consumer behavior. Meanwhile, market equilibrium is determined by solving demand (Qd = a−bPQ_d = a - bPQd​=a−bP) and supply (Qs = c+dPQ_s = c + dPQs​ = c+dP) functions, where their intersection defines the balance between supply and demand. (2) The research demonstrates how mathematical tools enhance the understanding of economic dynamics, offering precision in modeling and decision-making. The study underscores the significance of mathematics in optimizing economic analysis and contributing to effective policy formulation. This integration of theoretical mathematics and practical economics highlights its essential role in addressing real-world economic challenges.